Comparison of international medical costs for interventional pain treatment: a focus on Korea and Japan - Eun Young Lee; Hyung-sun Won; Miyoung Yang; Hyungtae Kim; Yeon-dong Kim (The Korean journal of pain, 2024)
Background: The rise in national health care costs has emerged as a global problem given the ever-aging population and rapid development of medical technology. The utilization of interventional pain management has, similarly, shown a continued rise worldwide. This study evaluates the differences in the medical costs in the field of interventional pain treatment (IPT) between two countries: Korea and Japan. Methods: Korean medical insurance costs for 2019 related to pain management focused on IPT were compared to those of Japan. Purchasing power parity (PPP) was used to adjust the exchange rate differences and to compare prices in consideration of the respective societies’ economic power. Results: The cost of trigger point injections in Japan was 1.06 times higher than that of Korea, whereas the perineural and intraarticular injection prices were lower in Japan. The cost of epidural blocks was higher in Japan compared to Korea in both cervical/thoracic and lumbar regions. As for blocks of peripheral branches of spinal nerves, the cost of scapular nerve blocks in Japan was lower than that in Korea, given a PPP ratio 0.09. For nerve blocks in which fluoroscopy guidance is mandatory, the costs of epidurography in Japan were greater than those in Korea, given a PPP ratio 1.04. Conclusions: This is the first comparative study focusing on the medical costs related to IPT between Korea and Japan, which reveals that the costs differed along various categories. Further comparisons reflecting more diverse countries and socio-economic aspects will be required.